Exploring the Role of Salt Supplementation on Milk Composition, Fatty Acids, and Insulin Response in Lactating Camels - Riyadh S. Aljumaah; Ahmed A. K. Salama; Mutassim M. Abdelrahman; Moez Ayadi; Gerardo Caja; Mohammed A. Alshaikh; Mohammed A. Al-Badwi; Abdulkareem M. Matar (Veterinary Sciences)
Camel milk is a valuable food source with unique nutritional properties and potential health benefits. This study investigated the influence of high dietary salt on milk composition and fatty acid (FA) profile as well as insulin regulation in dairy camels. Twelve multiparous female camels were used in a crossover design with two treatments: control concentrate (CON; 1.3% salt) and high-salt concentrate (SAL; 3.9% salt). Each period lasted 3 weeks, with camels switched between treatments in the second period. The measured variables included milk yield, milk composition, blood metabolites, and insulin levels in blood and milk. The SAL group exhibited higher (p < 0.01) water consumption. Nevertheless, milk yield and composition (fat, protein, lactose) remained unaffected. Notably, SAL camels had elevated blood insulin levels (p < 0.05) compared to the CON group, suggesting enhanced pancreatic activity possibly driven by osmotic balance changes. Milk FA profiles revealed a reduction in unsaturated fatty acids (UFA, p < 0.04), particularly monounsaturated (MUFA, p < 0.05) and odd-chain fatty acids (OCFA, p < 0.05). Furthermore, lipid quality indices such as the atherogenic index (p < 0.01) and the hypocholesterolemic/hypercholesterolemic FA ratio (h/H, p < 0.01) indicated a less favorable milk fat profile in the SAL group. These findings suggest that while moderate salt supplementation may not negatively impact milk yield in dairy camels, it alters both metabolic and milk fat composition variables, with potential implications for the nutritional quality of milk.